PENGARUH EVENT, CITRA WISATA, DAN E-WOM TERHADAP MINAT BERKUNJUNG KEMBALI PADA DESTINASI WISATA PANTAI PANDAWA - Sari, Putu Ratna Juwita; Kale, Gloria Velove (JURNAL BISNIS HOSPITALITI, 2024)
Pandawa has become popular because of its attractiveness and supported by social media which can disseminate the advantages of this beach. This research aims to see how the event , destination image and E-WOM influence the revisit intention to the Pandawa Beach. The research method used is quantitative with population of tourists who have visited the Pandawa Beach tourist attraction. The sampling technique used was purposive sampling,with a sample size of 95 respondents using the Slovin formula. The data collection technique uses  questionnaire distributed via GoogleForms which has been tested for validity and reliability. The data analysis technique uses multiple linear regression analysis. The results of this study concluded that attractiveness partially has a positive and significant effect on interest in returning to visit, tourism image partially influences revisit intention, E-WOM partially has a positiveand significant effect on revisit intention, and simultaneously event  , tourism image, and E-WOM have a positive significant effect on in revisit intention. Considering the phenomenon, it is important for Pandawa Beach management to cooperate with international parties in organizing events, providing more value to the uniqueness of tourism destinations and also strengthening the pleasant experience of visiting tourists in order to increase tourist revisits intention.